A relação teoria e prática na formação do licenciado em pedagogia : um estudo crítico da formação do professor reflexivo-pesquisador na proposta do curso de pedagogia da UNEB. - Viana, Marta Loula Dourado (2011)
The object of this research focuses on the relationship between theory and practice in the formation of the teacher majoring in Education, developing a critical study of the reflective teacher-researcher theory in the prospect of the Education Course at UNEB (Universidade Estadual da Bahia) specifically through the syllabus components research and Pedagogical Practice and Research and Training. These express themselves as possibilities of concreting the relationship between theory and practice making the pedagogy student realize themselves as potential reflexive researchers to different educational practices. This view of the reflective teacher-researcher has been justified in initial teacher education as an innovation by making the "criticism" to the traditional intellectualism and technicality, it points out to make the educational practice the main reference for the production of knowledge, therefore, a supposed solution to the historic dichotomy between theory and practice in pedagogy and teacher formation. From this perspective, we raise the following issue: what conception of theory and practical bases the training of graduate educational students in the UNEB and, to what extent, this view has elements for analysis and effective intervention on educational practice with ways to overcome the historical dichotomy between theory and practice? Thus, the objective of this research is to examine the pedagogical rationale underlying the design theory and practice in the syllabus and pedagogical training of teachers at UNEB prepared between the years 2007-2008, aiming to identify the contradictions and the possibilities to overcome into the perspective of historical-critical pedagogy. This study was based on literature research and reference documents from the historical and dialectical materialism, taking to the analysis of documents, specifically: the political pedagogical project and the UNEB syllabus, the teaching plans of the PPP and EP components, the CNE / CP 1 / 2006 and a document ANFOPE sent to the Brazilian National Council in 2004 on the DCN for the Education Majoring Course. The result is that there are four proposals for teacher training: 1) the ANFOPE in defense of common national base, the expansion of educational work into the non-integration in one school and bachelor's degree and, 2) group composed by Libâneo, Garrido and Franco, who advocate the formation of the teacher-researcher based on the "theory of reflective teacher-researcher" and in favor of specialization in order not to reduce the formation of the teacher to teaching, 3) Saviani‟s in defense of teacher and specialist teacher in the conjugated form, emphasizing the need for pedagogy and school appropriation of scientific knowledge, and finally, 4) the proposal approved by the CNE in 2006, which covers the positions of ANFOPE determining teaching as the basis of training, while it extends the teaching function for non-school education, and also the position of Libâneo, Franco and Garrido basing themselves on the pedagogy of reflective teacher-researcher. We identified the theory of reflective teacher-researcher as a consequence of the New School of Dewey and Piaget, who sought the definition of pedagogy as a science of education in a pluralistic and interdisciplinary perspective based on an epistemology of practice, i.e., under the logic of forms. Thus, after examining the proposal of UNEB, we conclude that it is based on the pedagogy of reflective teacher-researcher, confirming our hypothesis that the relation between theory and practice in teacher training at UNEB is now being understood as mere scope of the theory in practice, sometimes as a field of practice of building knowledge through research without the need to transcend the concrete-thinking, therefore, contrary to overcome the dichotomy between theory and practice, this training under the aegis of the reflective teacher-researcher indeed reinforces it, thus it values practice over the appropriation of scientific knowledge.